Regularity of Initial Ideal of Binomial Edge Ideals in Degree 2 and Their Powers (Contemporary Mathematics, 2024)
In this paper, we study the Castelnuovo-Mumford regularity of the initial ideal of binomial edge ideals in degree 2 ([in
Keywords: edge ideals; binomial edge ideals; Castelnuovo-Mumford regularity; polynomials ring